Knowledge Level Analysis of Pre-Service Biology Teacher on Fact and Myth Down Syndrome - Iseu Laelasari; Alfika Auliana; Sauki Fadlillah Nurus Sobah (Pedagogi Hayati, 2021)
Down syndrome is a genetic disorder caused by "nondisjunction of chromosomes" during cell division, which usually results in two copies of chromosome 21, but in down syndrome sufferers produce three copies of chromosomes to have 47 chromosomes. A lot of facts and myths about down syndrome as well as a great many pre-service biology teachers are misconceptions about down syndrome. The aim of this study is to measure the level of knowledge of pre-service biology teachers and to shed light on fact and myth down syndrome. Researchers used a descriptive method with a sample study of 30 pre-service biology teachers who were contrasting genetics courses and rigorously chosen with purposive sampling. Data is collected by the study instrument of a questionnaire with 20 questions and sent online using Google form. The result shows that the understanding of pre-service biology's teacher on facts and myth down syndrome with a low category of 3 %, a middle category of 66.7 %, and a high category of 30 %. As for the explanation of fact and myth down syndrome, it is synthesized with several scientific research sources.